Blogging the Virtual: New Geographies of Domination and Resistance In and Beyond Russia - Wolfe, Sven Daniel (My University, 2021)
Russia’s accelerating authoritarian turn has not ignored the internet, and in recent years, the Russian state has clamped down on internet activities that diverge from the statist line, employing a variety of strategies to dominate online spaces. Nevertheless, oppositional voices flourish on the Russian internet, taking shape in independent blogs and videos. This paper explores three political bloggers through surveillant and resistance assemblages, making sense of this contestation through an interpretation of the Deleuzian virtual that underscores the emancipatory potential of online activities for producing more egalitarian configurations, but also taking stock of the ways that these technologies have increased domination. Encompassing the blurriness between digital and corporeal spaces, the paper contributes by revealing new geographies of contestation against state strategies to dominate the Russian internet. Overlapping with but not corresponding to Russian territorial boundaries, these dynamics highlight shifting spaces of power and resistance in the increasingly illiberal world.